The value of the thromboelastometry heparinase assay (HEPTEM) in cardiac surgery - Meesters, Michael Isaäc; Lancé, Marcus Daniel; van der Steeg, Robin; Boer, Christa (Thrombosis and Haemostasis, 2015)
The thromboelastometry INTEM clotting time (CT) with heparinase (HEPTEM) is frequently used to detect residual heparin after cardiopulmonary bypass (CPB) in cardiac surgery. This study investigated whether the HEPTEM CT reflects the presence of residual heparin and the association of the protamine-to-heparin ratio to the INTEM and HEPTEM CT. We retrospectively evaluated thromboelastometry data that were obtained before CPB and after protamine infusion following CPB in two tertiary hospitals. The number of patients with an INTEM:HEPTEM ratio (IH-ratio) > 1, suggesting residual heparin, were quantified. Moreover, the influence of different protamine-to-heparin-dosing-ratios (P:H) on the INTEM and HEPTEM CT was evaluated in the clinical setting and in blood drawn from healthy volunteers. An INTEM:HEPTEM CT ratio > 1.1 was observed in 16% of the patients prior to CPB, and in 15% after protamine administration. Interestingly, 23% and 36% of the patients had an HEPTEM CT exceeding the INTEM CT before CPB and following protamine administration. The HEPTEM CT was longer than the INTEM CT in patients with a P:H-ratio of 1:1 (265 ± 132 vs 260 ± 246 s; p=0.002) or P:H-ratio of 1.3:1 (357 ± 174 vs 292 ± 95 s; p=0.001). Increasing P:H-ratios induced a prolonged HEPTEM CT in fresh blood. In conclusion, limited agreement was observed between INTEM and HEPTEM clotting time in the absence of heparin. INTEM comparison to HEPTEM may not always reliably reflect the presence of residual heparin, while protamine may additionally affect the latter test. These observations complicate HEPTEM results interpretation in clinical situations with suspected residual heparin effect after protamine.
Keywords: Thrombelastography; heparin; protamine; heparin lyase